Diallel analysis and prediction of untested maize single cross hybrids - José Lidércio Matias Júnior; Maurício Carlos Kuki; Carlos Alberto Scapim; Ronald José Barth Pinto (Bioscience Journal, 2019)
Popcorn (Zea mays everta) is a popular snack food and very appreciated in Brazil, presenting higher aggregate value when compared with field corn. The aim of this study were to identify superior inbred lines and single crosses hybrids (SH) for popcorn traits, as well as the prediction of the performance of untested single cross hybrids. Sixteen maize inbred lines were crossed in a 9x7 partial diallel, but it was possible to evaluate 47 single crosses in two distinct locations. Predicted genetic values, diallel analysis and the prediction of untested HS were performed by mixed models. Deviance effects for treatments x locations were considered non-significant (p>0.05) for grain yield (GY) and popping expansion (PE), showing an average performance from the HS in the locations. Inbred lines P5-1, P3.3T, GER-P3, P9-1, P12-2 and GER-P12 were selected considering the general combining ability, and should be used for obtaining superior genotypes. Based on the non-additive effects, the single hybrid P3.3T x GERP-P12 was selected for grain yield and popping expansion, and could be exploited in future trials. Neither of the untested single crosses showed desirable performance for grain yield and popcorn expansion.